TINJAUAN YURIDIS TERHADAP EFEKTIVITAS PENANGANAN KEJAHATAN SIBER TERKAIT PENCURIAN DATA PRIBADI MENURUT UNDANG-UNDANG NO. 27 TAHUN 2022 OLEH KOMINFO - Yudistira, Muhammad; Ramadani, Ramadani (UNES Law Review, 2023)
Law Number 27 of 2022 concerning Personal Data Protection was passed by the President of the Republic of Indonesia on October 17, 2022 with the main aim of protecting people's personal data managed by electronic system operators (PSE), such as the Ministry of Communication and Information Technology (Kominfo), as well as preventing crimes committed by irresponsible individuals. The need to address the problem of data leakage is the main focus that must be addressed immediately with a definite and secure solution. With the enactment of this personal data protection law, it is expected to be an effective solution in dealing with the problem of personal data leakage that often occurs in Indonesia. This Personal Data Protection Act was created with the aim of protecting the privacy rights of individuals. The Academic Paper of the Personal Data Protection Law explains that "the right to privacy through the protection of personal data is a key element for individual freedom and dignity". Therefore, this personal data protection regulation is enacted to safeguard the interests of the public to avoid misuse of their personal data. The author applies a normative juridical approach method that involves analyzing each writing, rules, and its application, Kominfo collaborates with the Siberkreasi movement to provide digital education to the public. The goal is for people to be smarter in sorting information, not easily influenced by hoaxes, and less dependent on information that cannot be ascertained. Kominfo continues to collaborate with the police in law enforcement related to the spread of hoaxes. Cyber security has a very important role in protecting data security. This is because of the importance of maintaining the information stored and ensuring the data transmitted remains safe.